A CLINICAL TRIAL OF VIRTUAL REALITY IN PHYSICAL THERAPY FOR BURN PATIENTS: EFFECTS ON PAIN PERCEPTION - AHMED, S; WASEEM, MH; AHMED, Z; TABASSUM, R; AHMED, B; SIYAL, S; MUSTAFA, B; HASSAN, Z; MANGI, AA; ASHRAF, W; et al. (Biological and Clinical Sciences Research Journal, 2023)
In clinical contexts, virtual reality (VR) has demonstrated potential as a cognitive diversion technique to alleviate discomfort among patients undergoing challenging procedures, including physical rehabilitation for burn victims. However, the extent of research investigating the effectiveness of VR in reducing pain during physical therapy for burn patients is limited. This clinical trial was conducted at Civil Hospital’s burns unit in Hyderabad and involved 68 participants. Each participant underwent two 6-minute physical therapy sessions, one utilizing VR and the other without VR. After each session, participants provided feedback on their pain experience, which the treating therapist documented. Analysis of graphic rating scores revealed a significant decrease in pain levels during physical therapy with VR compared to physical therapy without VR. The average scores for pain rumination, worst pain intensity, and unpleasantness decreased from 5.99 to 3.88, 6.24 to 3.41, and 6.18 to 3.82, respectively. The paired t-test indicated a highly significant p-value of less than 0.001. The results of this study suggest that VR is a valuable tool for reducing pain during physical therapy for burn patients. Further research is necessary to explore the long-term effects of VR on pain management and its potential application in other clinical settings.